The impact of the Covid-19 pandemic on successful breastfeeding: analysis of the impact of Covid-19 on routine visits and breastfeeding plans at Kasih Medika - Cokorda Istri Mirayani Pemayun; I Nyoman Hariyasa Sanjaya; Firsta Sesarina Mintariani; Made Diah Vendita Sakuntari; Ni Nyoman Dewi Purwanti; NI Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Luh Md Dwi Laxmi Satriani; Ni Komang Anik Pirgantari; Ni Luh Putu Yulia Padmawati; Anak Agung Wahyu Putri Agustini (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2021)
Introduction: All human worldwide had a risk infected by a severe acute respiratory syndrome–coronavirus-2 (SARS-CoV-2), including pregnant woman. Nowadays, SARS-CoV-2 transmission is still not fully understood. Thus, this situation created anxiety particularly for mothers that planned to breast-feed their baby and did their routine hospital visit. Thus this research aimed to evaluate the impact of COVID-19 pandemic with the routine visits and breastfeeding plan. Methods: This study was carried out with cross sectional observational study at Kasih Medika Hospital. The routine visits were conducted on the 5th-10th of August 2020. This study used a questionnaire instrument with samples of pregnant and postpartum mothers. The inclusion criteria of the sample were all pregnant women and post-partum that registered in Kasih Medika Hospital, complete questionnaire data filled in. The exclusion criteria were the patient agreed to be the research sample. All of the data was analyzed descriptively by using SPSS 25 and was presented by frequency. Results: All of the patients felt anxious with different stages of anxiety. COVID-19 affects 18% of patients who reduce their routine visits to Kasih Medika, while 82% keep visiting as scheduled. The COVID-19 pandemic had an insignificant effect on breastfeeding plans. This can be seen from only 27% of all respondents who are afraid of their breastfeeding plans. However, in the primigravida population, 45.45% of respondents were worried about their breastfeeding plan. Although in multigravida and post-partum, it was found that 90.90% were not afraid of their breastfeeding plans during the COVID-19 period. Conclusion: Our research established that COVID-19 reduces pregnant women's attendance to hospital, and patient primigravida was mainly afraid to do breastfeeding plans rather than multigravida patients. In contrast, mostly multigravida